Coinfection of Cytomegalovirus and Cryptosporidiosis in a Patient With AIDS. Issue 10 (October 2019) - Conner, Michael; Joshi, Tejas; Veerisetty, Sai Sruthi; Hutchings, John
Abstract : ABSTRACT: Patients with poorly controlled human immunodeficiency virus are subject to a wide range of opportunistic infections. Cryptosporidium is a parasitic gastrointestinal infection associated with chronic and life-threatening diarrhea in patients with acquired immunodeficiency syndrome. Cytomegalovirus colitis is a serious complication caused by reactivation of the virus, leading to viremia and end-organ disease by hematogenous spread. Both diseases can be fatal in less than 4 months. We present an example of a comprehensive investigation in a patient with symptoms that could not be explained in a single diagnosis.